The superconducting transition temperature for P-doped hydrogenated penta-graphene. (4th May 2021) - Einollahzadeh, Hamideh; Fazeli, Seyed Mahdi
Abstract: In this paper, we theoretically study superconductivity in hydrogenated penta-graphene (HPG). HPG has thermodynamical, mechanical and structural stability. By decreasing the Fermi energy of HPG, both manually and p-doping, we get strong density of states at the Fermi level. Therefore, one could expect that decreasing the Fermi energy may increase the superconducting transition temperature similar to graphane. We predict the superconducting transition temperature ( T C ) about 90 K for B-doped HPG. This high superconducting transition temperature suggests that p-doped HPG could be a decent candidate for a nanoscale superconductor.